Study on current practice of construction waste management system in Gambang, Kuantan, Pahang - Nur Fatin Aqilah, Mat Zin (2016)
Malaysian construction industry had shown a robust growth nowadays and it gives positive impact to the nation. Construction waste becomes a global issue facing by practitioners and researchers around the world. Waste can affects success of construction project significantly. Moreover, the increasing generation of construction wastes has caused significant impacts to the environment and aroused growing public concern in the local community. One of the objectives for this research is to characterize and quantify of construction waste generated in Gambang construction area. The standard procedure method was followed to conduct this research. Base on the research objective, the result shown that the generated steel waste ranged from 0.65% - 14.62%. For generated timber waste ranged 0.45% - 10.86%, the plastic waste ranged from 0.09% - 7.26%, the paper waste ranged from 0.15% - 2.24%, and others generated waste ranged from 0.18% - 47.68%. The result shown that there was lot of waste generated that was not managed properly in construction site. Therefore, the proper waste minimization is needed to control the quantity of construction waste produced.